If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 6 = 16 Reorder the terms: 6 + -5x = 16 Solving 6 + -5x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5x = 16 + -6 Combine like terms: 6 + -6 = 0 0 + -5x = 16 + -6 -5x = 16 + -6 Combine like terms: 16 + -6 = 10 -5x = 10 Divide each side by '-5'. x = -2 Simplifying x = -2
| 1.4(5x-0.3)= | | =1.4(5x-0.3) | | -5+6=16 | | 2x^3+4x^2+3x+6=0 | | 2z=1.3+1.5 | | x^2-x+21=0 | | 3b+2=21 | | 8n-(2n+7)=29 | | 3k^2+14k-5=0 | | p+2q=10 | | -5(f+7)=3(3f+-1) | | -4(r+3)=-70 | | 3x+5+3x+5+x+x=66 | | 2x-6x+8x-9x= | | (2x+3)(x+5)= | | m^2-28m+25=0 | | 6k-k=27-4 | | 43(x-172)=86 | | 5x^2+34+24=0 | | w^2+17w+16=0 | | 3x+5+x=66 | | 0.20(x+10)+1.40x=66 | | 0.5(8w-6)=17 | | 5(-1.2)-y=4 | | 8w+3=6 | | 3*l=5 | | 4x-6+x=54 | | 5y+1+3y=-5 | | 4=16t-16t^2 | | 9-33=-4z | | -3x-4z=17 | | 5z^2-3x-2=0 |